Prospective study of equine colic incidence and mortality - Tinker, Mary K.; White, N.A.; Lessard, Pierre; Thatcher, C.D.; Pelzer, K.D.; Davis, Betty; Carmel, D.K. (Wiley, 1997)
A prospective study of one year was conducted on 31 horse farms to obtain population based estimates of incidence, morbidity and mortality rates of equine colic. Farms with greater than 20 horses were enrolled by randomly selecting horse owners from 2 adjacent counties of Virginia and Maryland. Descriptive information for 1427 horses was collected at the initiation of the study and updated at 3 month intervals. Time on the farm during the study was tabulated for each horse. When colic was reported by the owner, investigators visited the farm to obtain information about the colic. The crude incidence density rate of colic was 10.6 colic cases/100 horse‐years, based on 104 cases/358,991 horse‐days. The median farm specific incidence density rate was 7 cases/100 horse‐years, and the range for individual farms varied from 0 to 30 colic cases/100 horse‐years. A specific diagnosis was not made for 84 (81%) of colic episodes. Seventy colic episodes (67%) were treated by a veterinarian. Drugs were used in 83 (80%) colic episodes, and 78 (75%) of colic cases were mild, requiring no treatment or resolving after only one treatment. Four horses required colic surgery. Fourteen (13%) horses had more than one episode of colic during the year. Mortality from all causes of death was 2.5 deaths/100 horse‐years, mortality rate for colic was 0.7 deaths/100 horse‐years. Proportional mortality rate of colic, 28%, was higher than for any other cause of death. Horses less than age 2 years or greater than age 10 years had lower incidence than horses age 2–10 years. No difference in colic risk between genders was identified. Arabian horses had the lowest and Thoroughbreds the highest breed specific incidence rates. Horses used for eventing, or in training had a statistically significant higher incidence rate of colic compared to mature horses with no use (pets, retired, on pasture with no stated purpose). Horses used for lessons or with no use had the lowest incidence rates.